Pengaruh Pendidikan Kesehatan terhadap Pengetahuan dan Sikap Ibu tentang Pemberian Makan Bayi dan Anak Stunting - Friska Nurul Hikmah; Tri Sunarsih (Oksitosin : Jurnal Ilmiah Kebidanan, 2024)
Stunting is a chronic problem associated with lack of energy and generally appears from the first 1000 days of life. The peak of child growth and development occurs in the first two years of life, making the role of mothers important in ensuring adequate nutritional intake for their babies. The purpose of this study was to evaluate the Effect of Health Education on Mothers' Knowledge and Attitudes regarding Infant and Child Feeding (PMBA) stunting in Ngalang Village, Gunungkidul, Yogyakarta. The research method used a pre-experimental design with a one group pretest-posttest approach. The study population involved all mothers with stunted children in Ngalang Village, Gunungkidul, Yogyakarta as many as 85 respondents, with 46 respondents taken as samples using purposive sampling techniques. Statistical analysis was performed using the Paired Sample T-test. The results of the analysis found that the average education of junior high school mothers was 21 people (45.7%). Bivariate analysis showed a p value in the knowledge variable of 0.000 (<0.05), and in the attitude variable of 0.027 (<0.05). The conclusion of this study is that health education has a positive influence on mothers' knowledge and attitudes related to stunting PMBA. The suggestion for future researchers is to be able to use a diverse sample in geographical aspects such as family income, to ensure representative results.